Diseño de un sistema SCADA para la adquisición de datos en la determinación de curvas características en bombas de torbellino conectadas en serie y en paralelo. - Gallegos Cuenca, Alex David (2022)
The development of this project had as main objective to implement a system that will allow the acquisition and monitoring of data in the determination of characteristic curves, this with the purpose of obtaining a reliable, functional and manipulable bank, which allows people to develop knowledge, skills on the characteristics of pumping systems in series and parallel with tables of results and graphs of the curves of the system. The implementation of the system has stages of study as the pressure measurement, this in the suction and discharge of the pump and the flow in the pump discharge, values that were used to choose the flow sensor and pressure transducers, for the acquisition and monitoring of data was performed in the free software, logo and delta HMI screen in which equations obtained after their respective calibration for each of the sensors were included. Tests were carried out with the outlet valve in different positions at the time of regulating the water flow, where the physical variables such as pressure and flow are visualized in the free software, which produces a record in the notepad of the values of pressure, flow, voltage, current, power and performance. The records allowed the realization of the characteristic curves and these determine that, in a pumping system connected in series, when the flow rate is at zero m3/s, its head is 91,03 m, and at a flow rate of 0,0003 m3/s, its head is 25,15 m, giving us a system efficiency of 6 %, in addition to a pumping system connected in parallel, when the flow rate is at zero m3/s, its head is 74,05 m, and at a flow rate of 0,00043 m3/s, its head is 41,4 m, giving us a system efficiency of 14 %.